1993
DOI: 10.1093/rheumatology/32.11.972
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of the Hip in Systemic Lupus Erythematosus: The Role of Magnetic Resonance Imaging

Abstract: The value of magnetic resonance imaging (MRI) in the early diagnosis of avascular necrosis (AVN) of the hip in SLE was investigated. Twenty females with severe SLE were studied prospectively. Each underwent 6-monthly X-rays, technetium -99m (Tc-99m) pyrophosphate bone scans and MRI of the hips over a 3-yr period. AVN was diagnosed in five hips of three patients (15%) during the study period. It was confirmed histologically in three hips of two patients who underwent core decompression. Radiological evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
0
12
0
5
Order By: Relevance
“…This situation is confounding because almost all SLE patients are treated with corticosteroids at some point, although they may be receiving cyclophosphamide, azathioprine, or nonsteroidal anti-inflammatory drugs at the time of presentation. The femoral head is most commonly affected, followed by the humeral head, femoral condyle, and tibial plateau (2,(35)(36)(37). Radiographs are usually normal in early AVN, and late changes of bone sclerosis indicate the presence of irreversible articular damage.…”
Section: Bonementioning
confidence: 99%
See 3 more Smart Citations
“…This situation is confounding because almost all SLE patients are treated with corticosteroids at some point, although they may be receiving cyclophosphamide, azathioprine, or nonsteroidal anti-inflammatory drugs at the time of presentation. The femoral head is most commonly affected, followed by the humeral head, femoral condyle, and tibial plateau (2,(35)(36)(37). Radiographs are usually normal in early AVN, and late changes of bone sclerosis indicate the presence of irreversible articular damage.…”
Section: Bonementioning
confidence: 99%
“…Prospective studies have demonstrated that MR imaging is superior to and more sensitive than radiography and scintigraphy for documenting early AVN, and MR imaging has been used to document osteonecrosis in asymptomatic SLE patients receiving high-dose corticosteroids (36,37). The MR imaging appearance of AVN correlates with the pathophysiologic features of the process.…”
Section: Bonementioning
confidence: 99%
See 2 more Smart Citations
“…Only a few reports in the literature have described the assessment of ON in juvenile SLE by MRI, and these studies combined paediatric and adult patients [14,15]. MRI appears to be a useful modality particularly in identifying pre-symptomatic ON lesions.…”
mentioning
confidence: 99%